Effects of an Early Postnatal Music Intervention on Cognitive and Emotional Development in Preterm Children at 12 and 24 Months: Preliminary Findings - Lejeune, Fleur; Lordier, Lara; Pittet, Marie P.; Schoenhals, Lucie; Grandjean, Didier; Hüppi, Petra S.; Filippa, Manuela; Borradori Tolsa, Cristina (Frontiers in Psychology, 2019)
Preterm birth is associated with a higher prevalence of neurodevelopmental deficits. Indeed, preterm children are at increased risk for cognitive, behavioral, and socio-emotional difficulties. There is currently an increasing interest in introducing music intervention in neonatal intensive care unit (NICU) care. Several studies have shown short-term beneficial effects. A recent study has shown that listening to a familiar music (heard daily during the NICU stay) enhanced preterm infants’ functional connectivity between auditory cortices and subcortical brain regions at term-equivalent age. However, the long-term effects of music listening in the NICUs have never been explored. The aim of this study was to evaluate at 12 and 24 months the effects of music listening in the NICU on emotional, attentional, and inhibition development in preterm children by comparing them to a preterm control group with no previous music exposure and to a full-term group. Participants were 44 children (17 full-term and 27 preterm). Preterm children were randomized to either music intervention or control condition (without music). The preterm-music group regularly listened to music from 33 weeks postconceptional age until hospital discharge or term-equivalent age. At 12 months, children were evaluated on the Bayley Scales of Infant and Toddler Development, Third Edition, then with 4 episodes of the Laboratory Temperament Assessment Battery (assessing expressions of joy, anger, and fear, and sustained attention). At 24 months, the children were evaluated with the same tests, and with 3 additional episodes of the Effortful Control Battery (assessing inhibition). Results showed that the scores of preterm children, music and control, differed from those of full-term children for fear reactivity at 12 months of age and for anger reactivity at 24 months of age. Interestingly, these significant differences were less important between the preterm-music and the full-term groups than between the preterm-control and the full-term groups. The present study provides preliminary, but promising, scientific findings on the beneficial long-term effects of music listening in the NICU on neurodevelopmental outcomes in preterm children, and more specifically on emotion mechanisms at 12 and 24 months of age. Our findings bring new insights for supporting early music intervention in the NICU.